Penetrating Extremity Trauma Endovascular versus Open Repair? - Kuwahara, Jeffery T.; Kord, Ali; Ray, Charles E., Jr. (Seminars in Interventional Radiology, 2020)
Penetrating extremity trauma (PET) accounts for an estimated 5–15% of trauma with vascular injury and these injuries are accountable for a significant percentage of trauma-related deaths. Historically, vascular injuries were best treated by open repair. While a defined selection criteria and a comprehensive algorithm have not been validated, the advancement of endovascular techniques, embolotherapy, and stent grafting have become viable options for the treatment of penetrating arterial extremity trauma in select patients. Advantages endovascular repair offers include decreasing mortality and morbidity associated with open repair, decreasing blood loss, decreasing iatrogenic injury such as nerve injury, and lower rate of wound infection. Patients stability, type of vascular injury, and lesion location are main factors help deciding between endovascular and open repair. Patient selection between endovascular and open repair should be determined by on a case-by-case situation, individual hospital guidelines, a multidisciplinary approach, and technical expertise.
Keywords: penetrating extremity trauma; arterial trauma; vascular injury; endovascular repair